An evolutionary concept analysis of learner-centered teaching - Oyelana, Olabisi; Olson, Joanne; Caine, Vera (My University, 2022)
Background An increasing emphasis on a paradigm shift from the traditional teacher-centered approach has led to the adoption of learner-centered teaching in many nursing education programs. However, the lack of consensus regarding the meaning warranted an analysis of learner-centered teaching. Objective The objective of this analysis was to clarify the concept of learner-centered teaching for nursing education and research. Design An evolutionary framework was used to perform a comprehensive review of both theoretical and empirical literature relevant to learner-centered teaching. An evolutionary concept analysis is a method of inquiry used to analyze the literature, with the purpose of identifying the attributes, antecedents, and consequences of a concept. Sample and setting Empirical and theoretical literature selected from the fields of education, nursing, and medicine. Methods A comprehensive review and analysis of theoretical and empirical publications from nursing, medicine and education disciplines provided a rich data source for this concept analysis. Results Four defining attributes of learner-centered teaching were identified: autonomy, empowerment, collaboration, and engagement. Four antecedents, three surrogate terms, eight related concepts, and nine primary consequences of learner-centered teaching were also identified. Exemplar cases of learner-centered teaching emerged from personal teaching practice experience and the empirical literature. Conclusions Learner-centered teaching is a complex concept with many aspects conceptualized or operationalized which make it difficult to authoritatively define the concept. However, the features of learner-centered teaching identified in this analysis offered a good basis for the evaluation, application, and further development of the concept in nursing.
Keywords: evolutionary concept analysis; nursing education; concept analysis; learner-centered teaching; theory development